SAT0459 Tocilizumab Therapy in Children with Systemic Juvenile Idiopathic Arthritis. Russian Experience. (23rd January 2014) - Alekseeva, E.; Denisova, R.; Valieva, S.; Bzarova, T.; Isayeva, K.; Sleptsova, T.; Mitenko, E.; Chistyakova, E.; Fetisova, A.
Abstract : Background: Systemic Juvenile Idiopathic Arthritis (sJIA) is classified as an acquired autoinflammatory disease. The interleukin-1 and interleukin-6 play a pivotal role in pathogenesis of this disease. The systemic manifestations as well as arthritis in sJIA are related to interleukin-6 action. Tocilizumab is promising drug for the treatment of systemic arthritis refractory to immunosuppressive drugs. Objectives: To evaluate safety and efficacy of tocilizumab treatment in children with systemic juvenile idiopathic arthritis. Methods: An open observational study in patients with sJIA taking tocilizumab. 75 patients were included into the study. Analysis of efficacy and safety tocilizumab therapy was performed in 75 patients. Median age was 7, 5 years (range; 0, 9 to 15 years) and median disease duration was 2, 5 years (range; 0.3 to 12 years). Tocilizumab was administrated intravenously at a dose of 8-12 mg/kg every 2 weeks during 2 months then every 4 weeks. All patients received DMARDs. Efficacy end points included the American College of Rheumatology (ACR) Pediatric criteria for improvement 30 (ACR30), ACR50, ACR70, ACR90 and criteria of inactive disease and remission. During the follow-up period, significant side-effects were sought and the reduction in oral prednisolone was recorded too. Results: The ACR Pedi 30, 50, 70 and 90 improvement were achieved by 100%, 90%, 80% and 55% of patients at Week 24 (n=72) and by 100%, 100%, 95% and 70% of patients at Week 52 (n=60), respectively. Inactive disease was achieved by 60% of patients at week 24 (n=72) and by 73% of patients at week 52 (n=61). Remission was achieved by 72% of patients (n=61). The mean dose of oral glucocorticoid was decreased at week 52. The frequently observed non-severe adverse events were nasopharyngitis, upper respiratory tract infections and gastroenteritis. No cases of opportunistic infections, malignancies or death were reported. There were three cases of pneumonia and cellulitis. 30 patients had incidences of neutropenia. Tocilizumab treatment was discontinued in 14 patients during the follow-up 52 weeks period. The causes for cancellation were relapse of disease (n=7), lack of efficacy (n=3), remission (n=1), parent's refusal (n=1), infusion reaction (n=1) and Crohn's disease (n=1). Dynamics in systemic features Conclusions: The results of the annual prospective observational study have shown the high efficacy of tocilizumab in patients with the severe sJIA. Drug induced remission of extra-articular manifestations, arthritis and normalized laboratory parameters of the disease activity without initiation of treatment with oral prednisolone and increase its dose, thus avoiding severe irreversible complications of glucocorticoid therapy. Tocilizumab induced disease remission in 72 % of patients at Week 52. Disclosure of Interest: None Declared